The Effect of Aromatherapy on Reduction of Physical Stress - Finedore, Mary; Hanson, Connor; McGee, Anna; Peterson, Carl; Petschen, Jennifer; White, Rebecca (Journal of Advanced Student Sciences (JASS), 2015)
Past research has shown that lavender is effective in reducing both physical and mental indicators of emotional stress but its effect on physical stress has yet to be determined. Physical and mental stress share many of the same physiological effects including increases in galvanic skin conductance, heart rate and blood pressure and it is likely lavender will lower these values following physical stress as it does following mental stress. To test this, participants were asked to bike until they reached 90% of their age-predicted heart rate max on two separate occasions - one with aroma and the other without. While not statistically significant, our study shows a trend for decreased recovery time in the aroma group for heart rate but not for blood pressure or GSR. Interestingly, this decrease was greater in the non-exercise group than a group that exercised at least 3 times a week.
An article that appeared in JASS, issue 2015
Keywords: acute; aerobic; aromatherapy; blood pressure; essential oil; exercise; Galvanic Skin Response; GSR; heart rate; lavender; physical stress; psychological stress; recovery time; stress; sympathetic nervous system